Register Editing Video di Aplikasi InShot: Kajian Sosiolinguistik - Fitri, Fajriani (CV. Eduartpia Publisher, 2025)
Video editing, there are many specific terms used by an editor. These terms form a register that can explain the use of features in the context of doing something in editing. This study aims to analyze the use of register in video editing in the InShot application. The method used is descriptive qualitative with Halliday's register theory approach. The results show that there are 16 open registers and 13 closed registers in InShot video editing application. The findings show that InShot app users adapt to the social context and reflect the language dynamics that develop among InShot app users. This research provides insights into how technology affects users' language use and comprehension in the context of video editing